E-Procurement Adoption in the Context of Malaysian Public Sector: The Way Forward - Kaliannan, Maniam (Journal of Malaysian and Comparative Law, 2011)
The edge of the Information Age, where information has become the cutting edge of global competition, has thrust the Information and Communication Technology (ICT) into the fore front of the national socio-economic development. ICT has been recognized as a strategic enabling tool to support the growth of the economy as well as enhance the quality of life of the population. The public sector in Malaysia is going through a period of rapid change. The government’s leading role in spearheading the surge forward into the information age has compelled the public sector to lead the way. The Government launched the Electronic Government (e-Government) initiative to reinvent itself to lead the country into the Information Age. Electronic Procurement or locally known as e-Perolehan was one of the projects that the government launched as part of the objective to reinvent the government in terms of service delivery through the use of ICT and to catalyze the successful development of the Multimedia Super Corridor (MSC) with ICT as one of the leading sectors of the economy. This paper examines the overall implementation of the e-Government initiative in Malaysia, with emphasis on the electronic procurement project known as e-Perolehan. E-Perolehan was started in the year 1999 and to date it has about 180,000 enabled suppliers, 2600 government agencies, six e-Perolehan modules and total transactions of more than RM11 billion. The general consensus amongst the buyer and seller communities is that e-Perolehan will become a catalyst towards a new and innovative procurement process within the Malaysian public sector. It is envisioned that within the next five years, more suppliers will grab the opportunity and benefit fully from the e-Perolehan initiative in Malaysia. Nevertheless, there are several issues that must be addressed by the relevant authorities to improve the procurement process in order to realise the objective of e-Perolehan system implementation.